2022
DOI: 10.1038/s41598-022-21760-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key biomarkers for STAD using filter feature selection approaches

Abstract: Gastric cancer (GC) is the fifth most common cancer and the third leading cause of cancer death worldwide. Discovery of diagnostic biomarkers prompts the early detection of GC. In this study, we used limma method combined with joint mutual information (JMI), a machine learning algorithm, to identify a signature of 11 genes that performed well in distinguishing tumor and normal samples in a stomach adenocarcinoma cohort. Other two GC datasets were used to validate the classifying performances. Several of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Effective feature selection methods help to identify potential molecular biomarkers for further research and to train precise classifiers for different tumour type/subtype classifications or diagnoses [ 23 ]. Studies have demonstrated the application of feature selection in genomic analysis of STAD and COAD based on TCGA and Gene Expression Omnibus (GEO) cohorts [ 24 , 25 ]. In this study, we applied MIFS algorithms and screened the top 20 candidate protein markers in distinguishing ESCA, STAD, and CRC tumour samples.…”
Section: Discussionmentioning
confidence: 99%
“…Effective feature selection methods help to identify potential molecular biomarkers for further research and to train precise classifiers for different tumour type/subtype classifications or diagnoses [ 23 ]. Studies have demonstrated the application of feature selection in genomic analysis of STAD and COAD based on TCGA and Gene Expression Omnibus (GEO) cohorts [ 24 , 25 ]. In this study, we applied MIFS algorithms and screened the top 20 candidate protein markers in distinguishing ESCA, STAD, and CRC tumour samples.…”
Section: Discussionmentioning
confidence: 99%